(3-2i)(x+iy)=2(x-2iy)+2i-1

Simple and best practice solution for (3-2i)(x+iy)=2(x-2iy)+2i-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-2i)(x+iy)=2(x-2iy)+2i-1 equation:


Simplifying
(3 + -2i)(x + iy) = 2(x + -2iy) + 2i + -1

Reorder the terms:
(3 + -2i)(iy + x) = 2(x + -2iy) + 2i + -1

Multiply (3 + -2i) * (iy + x)
(3(iy + x) + -2i * (iy + x)) = 2(x + -2iy) + 2i + -1
((iy * 3 + x * 3) + -2i * (iy + x)) = 2(x + -2iy) + 2i + -1
((3iy + 3x) + -2i * (iy + x)) = 2(x + -2iy) + 2i + -1
(3iy + 3x + (iy * -2i + x * -2i)) = 2(x + -2iy) + 2i + -1

Reorder the terms:
(3iy + 3x + (-2ix + -2i2y)) = 2(x + -2iy) + 2i + -1
(3iy + 3x + (-2ix + -2i2y)) = 2(x + -2iy) + 2i + -1

Reorder the terms:
(-2ix + 3iy + -2i2y + 3x) = 2(x + -2iy) + 2i + -1
(-2ix + 3iy + -2i2y + 3x) = 2(x + -2iy) + 2i + -1

Reorder the terms:
-2ix + 3iy + -2i2y + 3x = 2(-2iy + x) + 2i + -1
-2ix + 3iy + -2i2y + 3x = (-2iy * 2 + x * 2) + 2i + -1
-2ix + 3iy + -2i2y + 3x = (-4iy + 2x) + 2i + -1

Reorder the terms:
-2ix + 3iy + -2i2y + 3x = -1 + 2i + -4iy + 2x

Solving
-2ix + 3iy + -2i2y + 3x = -1 + 2i + -4iy + 2x

Solving for variable 'i'.

Reorder the terms:
1 + -2i + -2ix + 3iy + 4iy + -2i2y + 3x + -2x = -1 + 2i + -4iy + 2x + 1 + -2i + 4iy + -2x

Combine like terms: 3iy + 4iy = 7iy
1 + -2i + -2ix + 7iy + -2i2y + 3x + -2x = -1 + 2i + -4iy + 2x + 1 + -2i + 4iy + -2x

Combine like terms: 3x + -2x = 1x
1 + -2i + -2ix + 7iy + -2i2y + 1x = -1 + 2i + -4iy + 2x + 1 + -2i + 4iy + -2x

Reorder the terms:
1 + -2i + -2ix + 7iy + -2i2y + 1x = -1 + 1 + 2i + -2i + -4iy + 4iy + 2x + -2x

Combine like terms: -1 + 1 = 0
1 + -2i + -2ix + 7iy + -2i2y + 1x = 0 + 2i + -2i + -4iy + 4iy + 2x + -2x
1 + -2i + -2ix + 7iy + -2i2y + 1x = 2i + -2i + -4iy + 4iy + 2x + -2x

Combine like terms: 2i + -2i = 0
1 + -2i + -2ix + 7iy + -2i2y + 1x = 0 + -4iy + 4iy + 2x + -2x
1 + -2i + -2ix + 7iy + -2i2y + 1x = -4iy + 4iy + 2x + -2x

Combine like terms: -4iy + 4iy = 0
1 + -2i + -2ix + 7iy + -2i2y + 1x = 0 + 2x + -2x
1 + -2i + -2ix + 7iy + -2i2y + 1x = 2x + -2x

Combine like terms: 2x + -2x = 0
1 + -2i + -2ix + 7iy + -2i2y + 1x = 0

The solution to this equation could not be determined.

See similar equations:

| 3x/5+44=12x/25+8 | | 2x-3*4=-4 | | -149-7x= | | 4w+10=96 | | 3x/8-9=13+x/8 | | y/5.4=7.2 | | 2t^2+4t+8=0 | | -2y+7=Y | | 96/10 | | b/-8=23 | | 3x-14=2xd+10 | | 3.2x=6.8 | | 4w=102 | | x/9=135 | | 123+a=201 | | x-143=16 | | -7x=-133 | | 4w=90 | | 3x-10x=8x-30 | | y^2-6y-14=0 | | x^2+0.3x-0.1=0 | | 196=-14y | | -5*7+42/6 | | X^2-3x+2=2 | | 50x-13=55x-93 | | 3x^2+9x+1=0 | | 4x-10+x=180 | | 40n+(1.5n*5)=n | | 55/100x+504 | | (X-3)*(x-4)=12 | | 1.4=1.5-0.57 | | 15x+7-2x=-18 |

Equations solver categories